WIM BRIDGE SYSTEM EVALUATION ON ROAD PAVEMENT (A STUDY CASE OF SEMARANG TOLL ROAD SECTION ABC) - Sutjahjo, Kusumo Dradjad; Yazid, Firhan; Saputro, Danang Eko (POLITEKNIK NEGERI JAKARTA, 2020)
Semarang Toll Road Â Section ABC is one of many toll roads that are traversed by transport vehicles with a load exceeding the permit limit, especially for vehicles originating from the Port of Tanjung Mas. These overloaded vehicles cause a decrease in pavement condition due to pavement damage on Semarang Section ABC Toll Road Section. This study aims to determine the magnitude of the impact of overload vehicles on the remaining life of the road by using overload vehicle detection from the Weight in Motion Bridge system. The method used in this study refers to Bina Marga Pd T-05-2005-B and AASHTO 1993. Based on the results of the analysis that has been done, it can be concluded that there is a decrease in residual life due to overloading vehicles for the year 2022 in Section A, Line A reaches conditions of 26.93% and 37,46%; Section B Line A achieves pavement failure; Section C of Line A reaches 44.65% and 38.33% conditions; Section A Lane B reaches 32.02%; Section B Lane B achieves failure pavement; and Section C of Line B reaching 54.42% and 40.70%.